The Comparison of Factors Affecting Employee Loyalty of Generations X, Y and Z in Bangkok’s Hotel and Restaurant Industries - Wongprasurt , Supanee; Lee, Wing Shing (Centre For Tourism Planning and Development, 2024)
This study investigated the elements affecting job satisfaction and employee loyalty among employees from Generations X, Y, and Z in Bangkok's hospitality sector. These generational cohorts are projected to form a substantial portion of the labor force by 2025, each of which brings distinct work-related perspectives. This study aimed to identify the crucial factors influencing loyalty to enhance employee retention in the hotel and restaurant industries. Using Herzberg's Two-Factor Theory as a conceptual framework, data were gathered from 565 workers through a survey. The findings revealed that employee training, compensation, teamwork, and work-life balance had significant positive effects on job satisfaction, while employee empowerment did not show a substantial impact. Job satisfaction significantly influences employee loyalty. The results varied across generations: Generation Z valued teamwork and work-life balance significantly, with training showing marginal importance. For Generation Y, all four factors - training, compensation, teamwork, and work-life balance–were significant. Generation X prioritized work-life balance and compensation. These insights can benefit hospitality businesses by helping them develop targeted strategies for retaining employees and reducing turnover, potentially leading to enhanced productivity and financial performance. Moreover, this study offers valuable information about the motivations and preferences of the younger workforce generations, which can inform human resource management practices and policies in the industry.